2009
DOI: 10.1111/j.1442-2042.2009.02392.x
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of blunt renal trauma classification of Japanese Association for the Surgery of Trauma (JAST)

Abstract: Objectives:The Japanese Association for the Surgery of Trauma (JAST) classification is widely applied to select strategies in the treatment of blunt renal trauma in Japan. We retrospectively investigated the applicability of the JAST classification. Methods: The JAST classification comprises type I (subcapsular), type II (superficial), type III (deep) and pedicle vessel traumas. According to these criteria, we reviewed 70 patients with blunt renal trauma (types I, II, III and PV; n = 23, 22, 22 and 3, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 12 publications
0
19
0
2
Order By: Relevance
“…Sixteen patients were treated successfully with transcatheter arterial embolization in the 2 hospitals, and 15 of them were classified as type III renal injury. Thus, the authors believe that nephrectomy should be avoided in such patients because of the benefits offered by embolization [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen patients were treated successfully with transcatheter arterial embolization in the 2 hospitals, and 15 of them were classified as type III renal injury. Thus, the authors believe that nephrectomy should be avoided in such patients because of the benefits offered by embolization [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, conservative management for renal trauma is widely used today, and it is reported that most grade I and II, and stable parenchymal grade III and IV injuries were managed without any interventions. 2,12 In contrast, nephrectomy was carried out in 3.1% of all patients with renal trauma and 6.7% of patients initially undergoing AE. This shows that timely nephrectomy remains an important last resort despite the fact that AE has advanced.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen patients were treated successfully with transcatheter arterial embolization in the 2 hospitals, and 15 of them were classified as type III renal injury. Thus, the authors believe that nephrectomy should be avoided in such patients because of the benefits offered by embolization [22,23].…”
Section: Discussionmentioning
confidence: 99%